A challenge in diagnosing rash in HIV-positive MSM patient during overlapping epidemics in Central and Eastern Europe: Case report. (April 2022) - Bieńkowski, Carlo; Kowalska, Justyna D
In 2018-19, in Poland, there was a significant increase in the incidence of both measles and syphilis. In 2019, a 38-year-old HIV-positive MSM patient was admitted to a Department of Hospital for Infectious Diseases in Warsaw due to a rash on his trunk and palms. The patient had a past medical history notable for several syphilis episodes and hepatitis C twice. The patient was under care of the HIV Outpatient Clinic in the Hospital for Infectious Diseases in Warsaw since 2015, on fully effective antiretroviral therapy. Due to new syphilis onset with high titers and concomitant acute hepatitis C, he was hospitalized and treated with crystalline penicillin in a dose of 4x5 million units intravenously for 2 weeks along with benzathine penicillin 2.4 million units intramuscularly before being discharged. Ten days after being discharged home, the patient presented at the HIV clinic with fever and a non-itchy maculopapular rash that first appeared on the face and then also on the trunk and limbs. In presumptive diagnosis, three main conditions were taken into account: new onset of sexually transmitted disease, delayed allergic reaction to benzathine penicillin, and—in relation to a recent epidemical outbreak—measles. On physical examination, small white spots on the inner lining of the cheek were found (Koplik's spots). Swabs taken for measles RNA testing confirmed the diagnosis. Regarding the fact that both diseases may occur with a rash, they may pose a diagnostic challenge. Physicians should always include local epidemiological situation, including the possibility of overlapping outbreaks in differential diagnosis of nonspecific symptoms.